Pilot study of positive airway pressure usage, patient journey and program engagement for users of a digital obstructive sleep apnea program - Kumar, Shefali; Rudie, Emma; Dorsey, Cynthia; Caswell, Kimberly; Blase, Amy; Sert Kuniyoshi, Fatima; Benjafield, Adam V.; Sullivan, Shannon S. (Frontiers in Digital Health, 2023)
Purpose This single-arm, decentralized pilot study assessed patient journey, positive airway pressure (PAP) usage and program satisfaction for users of an entirely virtual telemedicine program for obstructive sleep apnea (OSA) diagnosis and management. This analysis focuses specifically on the subset of participants in the program who were diagnosed with OSA and prescribed PAP therapy. Methods The Verily Clinical Studies Platform was used for virtual screening, consent, and enrolling eligible patients from North Carolina and Texas. After completing the virtual OSA diagnosis process, participants diagnosed with OSA and prescribed PAP therapy downloaded the program's mobile app. The app featured tools such as educational content, live coaching support, and motivational enhancement. Results Of the patients included in this analysis (N = 105), the majority were female (58%), and white (90%). The mean time from first televisit to PAP initiation was 29.2 (SD 12.8) days and f 68 out of the 105 patients (65%) reached 90-day adherence. On average, patients used their PAP device for 4.4 h per day, and 5.4 h on days used. Engagement with the app was associated with higher rates of PAP adherence. Adherent individuals used the mobile app 52 out of the 90 days on average, compared to non-adherent individuals who used the app on 35 out of the 90 days on average (p = 0.0003). Conclusions All of the 105 patients in this program diagnosed with OSA and prescribed PAP therapy were able to efficiently complete the entire OSA diagnostic pathway. The majority of these individuals also were able to adhere to their prescribed PAP therapy and had clinically meaningful PAP usage rates over the 90 days of therapy. Future studies might further evaluate the impact of this type of end-to-end virtual program on longer-term adherence and clinical outcomes over time. Clinical Trial Registration https://clinicaltrials.gov/ct2/show/NCT04599803?term=NCT04599803&draw=2&rank=1, identifier NCT04599803.